Effects of different ischemic pressures on bar velocity during the bench press exercise: A randomized crossover trial - Dawid Gawel; Jakub Jarosz; Robert Trybulski; Michal Krzysztofik; Piotr Makar; João Guilherme Vieira; Grzegorz Trybek; Michal Wilk (Termedia Publishing House, 2024)
The main objective of this study was to evaluate the effects of different ischemic pressures applied during rest intervals on bar velocity during the bench press exercise. 10 resistance trained males (age = 23.2±2.7 years; body mass = 83.9±9 kg; body height = 181±5.2 cm; bench press 1 repetition maximum (1RM) = 125±16.4 kg; training experience = 5.4±3.4 years) participated in the study. During 4 experimental sessions, following a randomized crossover design, the subjects performed 5 sets of 3 repetitions of the bench press exercise with a load of 60% 1RM under conditions: with ischemia (50% or 80% of arterial occlusion pressure), with SHAM ischemia (20 mmHg) and without ischemia (control condition). For the ischemic conditions cuffs were applied before each set for 6.5 min and released 30 s before the start of the set as reperfusion (6.5 min ischemia + 0.5 min reperfusion). In the control condition, ischemia was not applied. The two-way repeated measures ANOVA showed no significant condition×set interaction for mean bar velocity (MV; p = 0.17) and peak bar velocity (PV; p = 0.66). There was also no main effect of condition for MV ( p = 0.58) and PV ( p = 0.61). The results indicate that ischemic or SHAM treatment (6.5 minutes ischemia or SHAM + 30 s reperfusion) does not affect mean and peak bar velocity during the bench press exercise regardless of the applied pressure.